Implementasi Kebijakan Pengawasan Penyelenggaraan Tugas Pegawai Kantor Kecamatan Cipocok Jaya, Kota Serang, Provinsi Banten - Anggraini, Yusniah (Jurnal Bina Praja, 2017)
One of the important management functions in government is supervision. However, supervisory issues are complex and complex, not as easy as what is being applied when applied, including its application in government agencies. Related to this, this study aims to find out the implementation of supervisory policy implementation of employee duties as well as identifying the supporting factors and obstacles in the District Office Cipocok Jaya Serang City. The method used in this research is qualitative descriptive method, with the informant is an employee in the district office environment. Data collection techniques used are interview techniques, and the instrument is in the form of interview guidelines. The data analysis technique is an inductive data analysis. The results of the field findings indicate that in the early stages of preparing the progress report lacking with the search for new data, most of the contents of the progress report have not really met the criteria or have the proper value, supervision for the work phenomenon is less followed up by the leadership, daily reporting, weekly, and the quarterly execution of the duties of employees is rarely implemented, evaluations conducted by the leadership so far prioritize the achievement of the number or target set (quantity standard), and the measurement of the quality of the work of the employee is only based on estimation only. Thus, the implementation of the policy of supervising the implementation of the duties of employees at the Cipocok Jaya District Office has been poor.